2018
DOI: 10.1155/2018/4135104
|View full text |Cite
|
Sign up to set email alerts
|

Association between Physical Exercise and Biomarkers of Oxidative Stress among Middle-Aged and Elderly Community Residents with Essential Hypertension in China

Abstract: This study aimed to investigate the role of different types and frequencies of physical exercise in biomarkers of oxidative stress among middle-aged and elderly community residents with essential hypertension in China. A community-based cross-sectional survey was undertaken in 7 subdistricts. Individuals, 45-79 years old, with essential hypertension (n = 402) and without cardiovascular disease (n = 1047) were included. Superoxide dismutase (SOD) activities and plasma levels of malondialdehyde (MDA) and 4-hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 51 publications
3
17
0
Order By: Relevance
“…Another previous study has reported that, with the increase of exercise frequency, the oxidative stress markers is improved in hypertensive individuals who participated in walking. This study has suggested that individuals with HT should engage in walking with a frequency of 4 or more days per week 57 . Thus, it is possible that the frequency of exercise in the ET program was insufficient to affect responsiveness.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Another previous study has reported that, with the increase of exercise frequency, the oxidative stress markers is improved in hypertensive individuals who participated in walking. This study has suggested that individuals with HT should engage in walking with a frequency of 4 or more days per week 57 . Thus, it is possible that the frequency of exercise in the ET program was insufficient to affect responsiveness.…”
Section: Discussionmentioning
confidence: 96%
“…This study has suggested that individuals with HT should engage in walking with a frequency of 4 or more days per week. 57 Thus, it is possible that the frequency of exercise in the ET program was insufficient to affect responsiveness. The decrease in MDA concentration in the ST was consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…A free radical is a molecule with an unpaired electron which is involved in lung damage, inflammation, reperfusion injury, cancer, cardiovascular disorders, atherosclerosis, aging and neoplastic diseases 18 They are also involved in autoimmune disorders like rheumatoid arthritis. 19 Many studies have investigated the role of antioxidant drugs and plant-derived compounds in the prevention of oxidative stress. 20 Evidence from our results, has shown that Newbouldia laevis also contains compounds with antioxidant potential.…”
Section: Discussionmentioning
confidence: 99%
“…On the same research line, in a large study involving 1449 subjects, SOD activity and plasma levels of malondialdehyde (MDA) and 4-hydroxynonenal (4-HNE) were determined. Results from a subpopulation of elderly subjects with hypertension showed that different types of PA induced an improvement in antioxidant activity and a reduction in MDA levels; however, these results were not always significant for all the types of PA advocated [22]. Other direct markers of inflammation are those related to the activation of the immune system, including the toll-like receptor (TLR) on white blood cells.…”
Section: Effect Of Pa On Inflammatory Markers and Oxidative Stress Mementioning
confidence: 99%